1993
DOI: 10.1007/bf01351475
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing, speech, and brainstem auditory-evoked potentials in spasmodic torticollis

Abstract: To explore the controversial "brainstem theory" of spasmodic torticollis, eight consecutively referred patients were examined. Three independent examinations were conducted on the same day: a videofluoroscopic barium swallowing examination, an instrumental speech examination, and a brainstem auditory-evoked potential (BAEP) analysis. Swallowing was normal in two patients; speech physiology, in five; and BAEPs, in all. Normal BAEPs refute the brainstem theory, while abnormalities of speech and swallowing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…[3][4][5] Similar observations have been documented before and after cranial neurectomies 6 7 and C1-C3 rhizotomies 8 9 in the above two types of cervical dystonias.…”
supporting
confidence: 76%
“…[3][4][5] Similar observations have been documented before and after cranial neurectomies 6 7 and C1-C3 rhizotomies 8 9 in the above two types of cervical dystonias.…”
supporting
confidence: 76%
“…Oropharyngeal function is usually investigated with the aid of videofluoroscopy. Clinical and videofluoroscopic evaluations have also indicated a high incidence of swallowing disorders in patients with CD before any treatment such as BoNT injection or rhizotomy [7][8][9]. In one study, swallowing abnormalities during video fluoroscopic examination were observed in over 50 % of CD patients [7].…”
Section: Diagnosis Of Dysphagia In Dystoniasmentioning
confidence: 99%
“…Dysphagia and dysarthria (which account for 10.2 % to 37 % and 0.9 % of complaints, respectively) are the two most common adverse effects of BoNT treatment for OMD [37,42]. Clinical and videofluoroscopic evaluations have also indicated a high incidence of swallowing disorders in CD patients before any treatment such as BoNT injection or rhizotomy [7][8][9]. In a study by Comella et al, although new radiologic changes occurred in 50 % of CD patients following BoNT treatment, clinically only 33 % of these patients reported new dysphagia symptoms.…”
Section: Diagnosis Of Dysphagia In Dystoniasmentioning
confidence: 99%
See 2 more Smart Citations